Teachers' Knowledge and Belief for Educating Sexuality for Kindergarten Students - Eka Oktavianingsih; Yulia Ayriza (The Faculty of Teacher Training and Education (FKIP), Universitas Sebelas Maret, Indonesia, 2018)
Teachers play an important role in children’s sexual development, but they have limited knowledge and different views about communicating sexuality. This study aims to determine teachers’ knowledge and beliefs related to sexuality education and to investigate the predictors of the beliefs. This research used quantitative and qualitative approach (mixed method). A total of 40 kindergarten teachers were asked to fill out a questionnaire describing teachers’ knowledge and demographic information, as well as a scale of beliefs about what teachers feel in teaching sexuality education. Interview techniques were used to gather information about the factors influencing teachers’ beliefs. Quantitative results showed that teachers had limited knowledge (M = 8.75, SD = 2.56) and had low belief (M = 2.75, SD = 0.28) in teaching sexuality education to children. Based on qualitative data, the learning resources in teaching sexuality was very limited. These results served useful evidence in developing appropriate and effective guidance programs to ensure teachers to educate sexuality education in a timely and appropriate manner to the children's development. Keywords: teachers, children, sexuality, knowledge, belief.